2011
DOI: 10.1039/c1lc20213h
|View full text |Cite
|
Sign up to set email alerts
|

Microfabricated polyester conical microwells for cell culture applications

Abstract: Over the past few years there has been a great deal of interest in reducing experimental systems to a lab-on-a-chip scale. There has been particular interest in conducting high-throughput screening studies using microscale devices, for example in stem cell research. Microwells have emerged as the structure of choice for such tests. Most manufacturing approaches for microwell fabrication are based on photolithography, soft lithography, and etching. However, some of these approaches require extensive equipment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 30 publications
1
59
0
Order By: Relevance
“…A mechanism for extraction of the cell aggregates from the individual microwells was not in place at this point, limiting our cell analysis in visual observation. These results match qualitatively the findings from previous research, 50 where mESCs were cultured under static conditions. However, in perfusion culture, the formed cell aggregates filled the microwells almost completely by day 5, which was 4 days earlier than in static culture.…”
supporting
confidence: 83%
See 3 more Smart Citations
“…A mechanism for extraction of the cell aggregates from the individual microwells was not in place at this point, limiting our cell analysis in visual observation. These results match qualitatively the findings from previous research, 50 where mESCs were cultured under static conditions. However, in perfusion culture, the formed cell aggregates filled the microwells almost completely by day 5, which was 4 days earlier than in static culture.…”
supporting
confidence: 83%
“…We have previously shown that microwell platforms could be easily and quickly manufactured using laser ablation of sticky polyester films. 50 Furthermore, we demonstrated that this material could be used in cell experiments without deleterious effects on the cell viability. The polyester l-assay chip presented here combines microwells for cell storage and 3D culture with a network of microfluidic channels.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other materials, including polydimethylsiloxane and polyurethane, have been applied to create three-dimensional cultures using photolithography (6,7). Additionally, poly(ethylene glycol) diacrylate, polymethylmethacrylate, poly(N-isopropylacrylamide) and polyester have been applied for the culture platform, while bypassing lithography (8)(9)(10). A previous study proved that three-dimensional culture systems have demonstrated the importance of intercellular interactions in regulating stem cell self-renewal and differentiation (3).…”
Section: Introductionmentioning
confidence: 99%